The structure of a Burkholderia pseudomallei immunophilin–inhibitor complex reveals new approaches to antimicrobial development - Norville, Isobel H. (2011)
Mips (macrophage infectivity potentiators) are a subset of immunophilins associated with virulence in a range of micro-organisms. These proteins possess peptidylprolyl isomerase activity and are inhibited by drugs including rapamycin and tacrolimus. We determined the structure of the Mip homologue [BpML1 (Burkholderia pseudomallei Mip-like protein 1)] from the human pathogen and biowarfare threat B. pseudomallei by NMR and X-ray crystallography. The crystal structure suggests that key catalytic residues in the BpML1 active site have unexpected conformational flexibility consistent with a role in catalysis. The structure further revealed BpML1 binding to a helical peptide, in a manner resembling the physiological interaction of human TGFβRI (transforming growth factor β receptor I) with the human immunophilin FKBP12 (FK506-binding protein 12). Furthermore, the structure of BpML1 bound to the class inhibitor cycloheximide N-ethylethanoate showed that this inhibitor mimics such a helical peptide, in contrast with the extended prolyl-peptide mimicking shown by inhibitors such as tacrolimus. We suggest that Mips, and potentially other bacterial immunophilins, participate in protein–protein interactions in addition to their peptidylprolyl isomerase activity, and that some roles of Mip proteins in virulence are independent of their peptidylprolyl isomerase activity.